[OP.4B.10] LEFT VENTRICULAR MASS AFTER RENAL TRANSPLANTATION - METAANALYSIS OF CROSS-SECTIONAL AND LONGITUDINAL STUDIES. (September 2016) - Schmidt, B.; Bergmann, K.; Kaufeld, J.; Melk, A.
Abstract : Objective: Left ventriuclar mass (LVM) is a strong predictor of cardiovascular events. In patients with chronic kidney disease and in patients on dialysis left ventricular hypertrophy is highly prevalent. Overcoming uremia by renal transplantation might improve LVM. However, after transplantation treatment with steroids and calcineurin inhibitors increases blood pressure and therefore might counteract the positive effect of restoring renal function. We performed a metaanalysis of the available evidence from observational studies in patientts after renal tranplantation. Figure. No caption available. Design and method: We used the terms left ventricular hypertrophy OR left ventricular mass, (renal OR kidney) and transplantation to search Medline without time limit. Search was restricted to articles published in english. Additional studies were identified from the references of the selected manuscripts. Random effects modells were used to compare the transplanted and non-trasplanted patient groups. Studies were separated in cross-sectional studies comparing transplanted patients with dialysis patients and healthy controls and longitudinal studies comparing the same patients before and after transplanataion. We used Comprehensive metaanalysis V2.2, Biostat, Englewood, USA for analyses. Results: We identified 6 studies comparing transplanted patient with dialysis patients. LVM was lower in the transplanted patients (Standardized difference in means 0.798 95% CI 0.087, 1, 508 p = 0.028). We identified 7 studies comparing transplanted patients with dialysis patients. The LVM was lower in the transplanted patients(Standardized difference in means 0.431, 95% CI 0.659–0.203, p < 0.001). Finallly we identified 20 studies comparing patients before and after transplantation, showing that LVM decreases after transplantation (standardized difference in means 0.347, 95% CI 0.421–0.273, p < 0.001). Conclusions: Patients after renal transplantation show lower LVM than patients on dialysis, but still higher LVM than healthy controls. This reflects that cardiovascular risk has improved after transplantation but still is higher than in the normal population.